2020
DOI: 10.21203/rs.2.24414/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review and meta-analysis of  Job stress among Iranian nurses

Abstract: Background: Job stress is the most important factor in reducing organizational productivity. Therefore, this study aimed to identify prevalence of job stress among nurses in Iran.Methods: This study was conducted using a meta-analysis. All published articles on prevalence of job stress among nurses in Iran until July 2018 were searched and collected using PubMed, Web of Science, Science Direct, CINAHL, PsychInfo, Scopus, Magiran, IranMedex and SID and Bibliography section of the retrieved papers and related jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This study also revealed a high level of perceived stress with about half of the respondents being stressed, which was higher compare to 32% and 43% obtained among medical doctors in Ibadan (Adeolu et al, 2016) and in Ile-Ife (Akinsulore et al, 2020), Nigeria respectively. This finding was lower in comparison with studies done in Portugal (50%) (Joaquim et al, 2017), Iran (78.4%), Saudi Arabia (66.2%) and United Kingdom (59%) (Kakemam et al, 2019;Isfahani et al, 2020). The outcomes of studies from different countries revealed variations in the prevalence of perceived stress among health care professionals.…”
Section: Perceived Stress Of the Respondentsmentioning
confidence: 56%
“…This study also revealed a high level of perceived stress with about half of the respondents being stressed, which was higher compare to 32% and 43% obtained among medical doctors in Ibadan (Adeolu et al, 2016) and in Ile-Ife (Akinsulore et al, 2020), Nigeria respectively. This finding was lower in comparison with studies done in Portugal (50%) (Joaquim et al, 2017), Iran (78.4%), Saudi Arabia (66.2%) and United Kingdom (59%) (Kakemam et al, 2019;Isfahani et al, 2020). The outcomes of studies from different countries revealed variations in the prevalence of perceived stress among health care professionals.…”
Section: Perceived Stress Of the Respondentsmentioning
confidence: 56%